On Philosophy as a Gendered Institution: Ri-Practicing the Order of Philosophical Discourse through Adriana Cavarero’s Concept of Sexual Difference (Nóema, 2023)
This article focuses on the analysis of the way philosophy as an institution has asserted itself as neutral but is, in fact, gendered and sexed through masculine lenses. The analysis draws on an understanding of the concept of «sexual difference» as theorized by Adriana Cavarero. By employing the conceptual framework of philosophy as a «practice» intertwined with life practices developed by Carlo Sini, and that of the «order of discourse» provided by Michel Foucault, this article explicates the premises and consequences of the order of discourse in the elaboration of concepts. Subsequently, it explores possibilities for rethinking this order through the theoretical praxis of Adriana Cavarero, and its relevance for the current context. This article hypothesizes that the claim of neutrality and universality of philosophy is contradicted by the awareness that the thinking subject is a living being whose life experience, including their sexed and gendered being, permeates both the world of life and the world of knowledge. Consequently, the formation of philosophical concepts is bound to the gendered perspective of the subject who elaborates them. As a result, the neutral order of discourse represents both a challenge to women’s thinking and an opportunity to be re-practiced. Finally, the article offers a reflection on the institutional changes between the 1980s, the reference period for Cavarero’s theoretical formulation that the article focuses on, and the current situation of Italian universities concerning gender issues.
Keywords: Sexual difference; Philosophical practice; Gendered institution; Adriana Cavarero; Order of discourse